Advances in orebody modelling and strategic mine planning 1 : old and new dimensions in a changing world - Dimitrakopaulos, Roussos (Spectrum series (Carlton, Vic.) ; no. 17., 2010)
"In an ever-changing world of uncertain markets, mismatches between demand and reserve base growth, new emerging technologies, and new technical problems and their solutions, this book represents a contribution to both old and new dimensions of a most intricate, complex, challenging and critically important technical part of mining ventures and the industry. These and other issues add complexity and uncertainty to the already challenging domains of orebody modelling and strategic mine planning, which are arguably the backbone of our industry. This volume comprises 43 papers under the following topics: Modelling and Planning in the New World; Modelling Orebodies and Applications; Mining Optimisation and Case Studies; Large-Scale Integrated Applications; Uncertainty Models and Recoverable Reserves; Optimisation is Moving Underground and The New World and Strategic Innovation."--Pub. desc.